2014
DOI: 10.1016/j.gca.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Li/Mg systematics in scleractinian corals: Calibration of the thermometer

Abstract: We show that the Li/Mg systematics of a large suite of aragonitic coral skeletons, representing a wide range of species inhabiting disparate environments, provides a robust proxy for ambient seawater temperature. The corals encompass both zooxanthellate and azooxanthellate species (Acropora sp., Porites sp., Cladocora caespitosa, Lophelia pertusa, Madrepora oculata and Flabellum impensum) collected from shallow, intermediate, and deep-water habitats, as well as specimens cultured in tanks under temperature-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
152
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(168 citation statements)
references
References 98 publications
(144 reference statements)
15
152
1
Order By: Relevance
“…While there is some uncertainty in the mechanism of Mg 2+ incorporation into aragonite (Montagna et al, 2014), the K D nevertheless serves as an empirical measure of the distribution of Mg/Ca between aragonite and seawater under various conditions. DeCarlo et al (2015) reported K D for Sr/Ca from these same samples, and here we follow the same calculations for K Mg/Ca D using the Mg/Ca data from Holcomb et al (2016), except for the slight modifications to the calculations described below.…”
Section: Mg/ca Partitioning Between Aragonite and Seawatermentioning
confidence: 99%
“…While there is some uncertainty in the mechanism of Mg 2+ incorporation into aragonite (Montagna et al, 2014), the K D nevertheless serves as an empirical measure of the distribution of Mg/Ca between aragonite and seawater under various conditions. DeCarlo et al (2015) reported K D for Sr/Ca from these same samples, and here we follow the same calculations for K Mg/Ca D using the Mg/Ca data from Holcomb et al (2016), except for the slight modifications to the calculations described below.…”
Section: Mg/ca Partitioning Between Aragonite and Seawatermentioning
confidence: 99%
“…Instead, culture experiments and core top studies have shown that the Li/Ca ratio of foraminifera is influenced by the solution Li/Ca ratio, DIC concentration, and possibly the growth rate (Delaney et al, 1985;Hall and Chan, 2004;Hathorne and James, 2006;Lear and Rosenthal, 2006;Vigier et al, 2015). In contrast, the Li/Mg ratio of corals and foraminifera is more strongly related to temperature than Li/Ca and has been recently proposed as being a reliable proxy for ocean temperature (Bryan and Marchitto, 2008;Case et al, 2010;Montagna et al, 2014;Rollion-Bard and Blamart, 2015;Fowell et al, 2016). The Li/Ca ratio of mollusks might be controlled by a combination of vital effects, growth rate, changes in ocean productivity, and/or dissolution of riverine fine sediments within the ocean (Füllenbach et al, 2015;Thébault et al, 2009;Thébault and Chauvaud, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Variation of the Sr/Ca-SST dependency limits the proxy accuracy and therewith its utility, particularly in regions where seasonal temperature changes are limited. Recently, the Li/Mg ratio in aragoniticscleractinian coral skeletonshas been shown to be a species independent SST proxy that could complement previous temperature proxy (Case et al, 2010;Hathorne et al, 2013a;Montagna et al, 2014).To reconstruct the pH of the seawater, the U/Ca ratio in tropical corals was proposed (Inoue et al, 2011) but its strong sensitivity to temperature clearly limitspaleopH applications. Contrarily, boron isotopes in Porites sp.…”
Section: Introductionmentioning
confidence: 99%